THE RIGHT TO FORM AND TO JOIN TRADE UNIONS AS DEFINED IN INTERNATIONAL LEGAL INSTRUMENTS - Majhoshev, Andon; Krusharska Velinovska, Katerina (Journal of process management and new technologies, 2017)
The right of workers to form and to join trade unions is one of the most important international labour standards. This means that employees, no matter where they are employed (public or private sector), have the right to form their own organizations (unions). Apart from the employees, employers also have the right to form and join in employers’ associations. The right of employees and employers to organize is based on the following principles: voluntariness, autonomy and democracy. The general objective of the formation of unions and employers’ associations is to protect the rights and interests of members of the union and the employers’ association, as well as their promotion in an organized manner. The provision and guarantee of union and workers’ rights are guaranteed by a number of international and regional legal instruments (conventions, recommendations, regulations), such as ILO, UN, Council of Europe and the European Union, which will be analysed further in this paper. The main objective arising from these documents is to improve the position of workers and their protection. Within the paper, we will also analyse the most important legal acts of the Republic of Macedonia concerning the right to join unions. By analysing the content of the national labour legislation, we will determine the extent to which the international labour law is being implemented. Moreover, the paper will analyse the basic principles underlying union organization and association.